GFAP in early multiple sclerosis: A biomarker for inflammation. (14th September 2017) - Kassubek, Rebecca; Gorges, Martin; Schocke, Michael; Hagenston, Viktoria A.M.; Huss, André; Ludolph, Albert C.; Kassubek, Jan; Tumani, Hayrettin
Highlights: CSF-GFAP is significantly higher both in RRMS and in CIS than in healthy controls. CSF-GFAP correlates with the intensity of gadolinium-enhancement in MRI. CSF-GFAP is a candidate as a biomarker for acute inflammation in MS. Abstract: Objective: The role of Glial Fibrillic Acidic Protein (GFAP) as a potential biomarker for relapsing-remitting multiple sclerosis (RRMS) and clinically isolated syndrome (CIS) has been controversially discussed. The aim was to characterize the added value of GFAP levels in the CSF of RRMS and CIS patients in correlation with MRI lesion load. Materials & methods: GFAP levels in the CSF from 18 patients with RRMS, 8 patients with CIS and 35 controls were analyzed together with MRI data for acute and chronic inflammatory lesion load. Results: GFAP levels of patients vs. controls were higher ( p  = 0.005), while there was no difference between GFAP levels in RRMS and CIS. There was no correlation between the number of supra- or infratentorial gadolinium enhancing lesions and GFAP levels, while there was a correlation between GFAP levels with infratentorial chronic inflammatory lesion load ( p  = 0.0035). Most importantly, a highly significant correlation could be observed between GFAP levels and the intensity of gadolinium-enhancement as a parameter for the acute activity of inflammatory processes ( p  = 0.0002). Conclusions: GFAP seems to be a useful biomarker for highly active acute inflammation in patients with RRMS as well as with CIS.